2020
DOI: 10.3389/fnagi.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dynamic Complexity of BOLD Signals Differentiates Mild Cognitive Impairment From Normal Aging

Abstract: Mild cognitive impairment (MCI) is characterized as a transitional phase between cognitive decline associated with normal aging and Alzheimer's disease (AD). Restingstate functional magnetic resonance imaging (fMRI) measuring blood oxygenation leveldependent (BOLD) signals provides complementary information considered essential for understanding disease progression. Previous studies suggested that multi-scale entropy (MSE) analysis quantifying the complexity of BOLD signals is a novel and promising method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Several authors have attempted to compare the functional complexity of groups and subjects by other means (Ostwald and Bagshaw, 2011;Liu et al, 2013;McIntosh et al, 2014;Grieder et al, 2018;Zheng et al, 2020;Xin et al, 2021), but they may overlook interregional statistical dependencies and thus risk erroneous estimates of region-specific complexity. A rigorous means of quantifying the functional complexity alterations which characterize psychiatric disorders remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have attempted to compare the functional complexity of groups and subjects by other means (Ostwald and Bagshaw, 2011;Liu et al, 2013;McIntosh et al, 2014;Grieder et al, 2018;Zheng et al, 2020;Xin et al, 2021), but they may overlook interregional statistical dependencies and thus risk erroneous estimates of region-specific complexity. A rigorous means of quantifying the functional complexity alterations which characterize psychiatric disorders remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous resting-state functional MRI studies have exhibited reduced functional connectivity of ACC in patients with MCI/AD compared with the HC group ( Cao et al, 2020 ; Ibrahim et al, 2021 ). A recent study, which used sample entropy (SE) in measuring the complexity of dynamic BOLD signal, has further indicated that individuals with lower SE were associated with a 3.4-fold increased risk of progression to AD in comparison with those with high SE ( Zheng et al, 2020 ). Our results further showed reduced DA of right ACC in the SCD vs. HC groups.…”
Section: Discussionmentioning
confidence: 99%
“…93 It has also been shown that reduced BOLD signal complexity (quantified by multiscale entropy analysis) can be detected at the MCI stage and that reduced BOLD signal complexity in the anterior cingulate corrostrum is associated with the risk of progression to AD. 94 The causes of BOLD signal low-frequency fluctuation are complex, not only include neuronal activity itself but also being influenced by some interference factors, some of which can be filtered, such as breathing and heartbeat pulsation. 95 Tong et al 95 found that there was also a kind of fluctuation spreading along with bloodstream and had a frequency similar to neural activity fluctuations, which affected the recognition of simple neural activity, and thus affected the quantification of brain networks.…”
Section: 24mentioning
confidence: 99%
“…Some studies have shown that BOLD variation is increased in AD patients, which needs to be further explored by expanding the sample size 93 . It has also been shown that reduced BOLD signal complexity (quantified by multiscale entropy analysis) can be detected at the MCI stage and that reduced BOLD signal complexity in the anterior cingulate corrostrum is associated with the risk of progression to AD 94 . The causes of BOLD signal low‐frequency fluctuation are complex, not only include neuronal activity itself but also being influenced by some interference factors, some of which can be filtered, such as breathing and heartbeat pulsation 95 .…”
Section: Progress In Mr Imaging Of Admentioning
confidence: 99%